Expanding the triangle of U: comparative analysis of the Hirschfeldia incana genome provides insights into chromosomal evolution, phylogenomics and high photosynthesis-related traits - Hoang, Nam V.; Walden, Nora; Caracciolo, Ludovico; Luoni, Sofia Bengoa; Retta, Moges; Li, Run; Wolters, Felicia C.; Woldu, Tina; Becker, Frank F. M.; Verbaarschot, Patrick; Harbinson, Jeremy; Driever, Steven M.; et al. (Annals of botany, 2024)
The Brassiceae tribe encompasses many economically important crops and exhibits high intra- and interspecific phenotypic variation. After a shared whole-genome triplication (WGT) event (Br-α, ~15.9 Mya), differential lineage diversification and genomic changes contributed to an array of divergence in morphology, biochemistry and physiology underlying photosynthesis-related traits. Here, the C3 species Hirschfeldia incana is studied because it displays high photosynthetic rates in high-light conditions. Our aim was to elucidate the evolution that gave rise to the genome of H. incana and its high-photosynthesis traits.We reconstructed a chromosome-level genome assembly for H. incana (Nijmegen, v.2.0) using nanopore and chromosome conformation capture (Hi-C) technologies, with 409 Mb in size and an N50 of 52 Mb (a 10× improvement over the previously published scaffold-level v.1.0 assembly). The updated assembly and annotation were subsequently used to investigate the WGT history of H. incana in a comparative phylogenomic framework from the Brassiceae ancestral genomic blocks and related diploidized crops.Hirschfeldia incana (x = 7) shares extensive genome collinearity with Raphanus sativus (x = 9). These two species share some commonalities with Brassica rapa and Brassica oleracea (A genome, x = 10 and C genome, x = 9, respectively) and other similarities with Brassica nigra (B genome, x = 8). Phylogenetic analysis revealed that H. incana and R. sativus form a monophyletic clade in between the Brassica A/C and B genomes. We postulate that H. incana and R. sativus genomes are results of hybridization or introgression of the Brassica A/C and B genome types. Our results might explain the discrepancy observed in published studies regarding phylogenetic placement of H. incana and R. sativus in relationship to the ‘triangle of U’ species. Expression analysis of WGT retained gene copies revealed sub-genome expression divergence, probably attributable to neo- or sub-functionalization. Finally, we highlight genes associated with physio-biochemical-anatomical adaptive changes observed in H. incana, which are likely to facilitate its high-photosynthesis traits under high light.The improved H. incana genome assembly, annotation and results presented in this work will be a valuable resource for future research to unravel the genetic basis of its ability to maintain a high photosynthetic efficiency in high-light conditions and thereby improve photosynthesis for enhanced agricultural production.
Artikelversion: 19. November 2024
Gesehen am 14.05.2025